Introducing a new specifier for functional somatic disorder: a psychodynamic approach to investigating emotional factors - Maroti, Daniel (Frontiers in Psychiatry, 2025)
Functional Somatic Disorders (FSD) present a significant challenge in the health-care system, characterized by persistent, distressing physical symptoms without sufficient medical or psychiatric explanations. This conceptual analysis explores the psychodynamic approach to understanding emotional factors influencing FSD, proposing a new psychological specifier. While current diagnostic frameworks, such as DSM-5’s Somatic Symptom Disorder (SSD) and ICD-11’s Bodily Distress Disorder (BDD), incorporate psychological components, they do not fully address emotional dynamics. This paper advocates for integrating emotional factors into diagnostic criteria. The proposed specifier focuses on emotional factors such as unresolved grief, trauma, and unmet needs, which can exacerbate or cause somatic symptoms. Six signs indicative of emotional influence on somatic symptoms are discussed, emphasizing a collaborative investigative approach. Incorporating this specifier could enhance diagnostic accuracy, treatment planning, and patient outcomes by acknowledging the interplay between emotional and physical health.